1999
DOI: 10.1016/s0002-9440(10)65401-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Proliferation and Altered Differentiation in Osteoblasts from Genetically and Clinically Distinct Craniosynostotic Disorders

Abstract: Craniosynostoses are a heterogeneous group of disorders characterized by premature fusion of cranial sutures. Mutations in fibroblast growth factor receptors (FGFRs) have been associated with a number of such conditions. Nevertheless , the cellular mechanism(s) involved remain unknown. We analyzed cell proliferation and differentiation in osteoblasts obtained from patients with three genetically and clinically distinct craniosynostoses: Pfeiffer syndrome carrying the FGFR2 C342R substitution , Apert syndrome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
49
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 47 publications
12
49
0
3
Order By: Relevance
“…We and others (37,38) previously found that FGF signaling activates PLC␥-PKC signaling in osteoblasts. To determine the potential role of PKC in osteoblast differentiation induced by FGFR2 activation in mesenchymal cells, we analyzed PKC activity in C3H10T1/2 cells stably expressing WT or MT Fig.…”
Section: Pkc Signaling Is Involved In Mt Fgfr2-mediated Osteoblast DImentioning
confidence: 74%
“…We and others (37,38) previously found that FGF signaling activates PLC␥-PKC signaling in osteoblasts. To determine the potential role of PKC in osteoblast differentiation induced by FGFR2 activation in mesenchymal cells, we analyzed PKC activity in C3H10T1/2 cells stably expressing WT or MT Fig.…”
Section: Pkc Signaling Is Involved In Mt Fgfr2-mediated Osteoblast DImentioning
confidence: 74%
“…Finally, osteoblasts derived from human synostotic sutures (ie, isolated and syndromic sutures) demonstrate greater basal levels of type I collagen and noncollagenous matrix molecules than control osteoblasts. [41][42][43] Taken together, these studies suggest that alterations in the expression of osteogenic cytokines (ie, FGF-2 and TGF-␤1) and extracellular matrix molecules likely determine the fate of the overlying cranial sutures. These conclusions are supported by our current study.…”
Section: Discussionmentioning
confidence: 99%
“…The protein kinase C (PKC) pathway is involved in the control of sodium-dependent phosphate transport (Suzuki et al 2000) and expression of N-cadherin in calvarial osteoblasts (Debiais et al 2001). Mutations in Fgfr2 that cause Apert syndrome induce constitutive activation of PKC in human calvarial osteoblasts (Fragale et al 1999;Lomri et al 2001). This signaling pathway is responsible for the increased differentiation and apoptosis in mutant osteo-blasts (Lemonnier et al , 2001a.…”
Section: Fgf Signaling Pathways In Intramembranous Bone Formationmentioning
confidence: 99%
“…In murine calvarial cells, transfection of the Fgfr2 S252W (Apert mutation) gene inhibits cell differentiation and increases proliferation (Mansukhani et al 2000). In human osteoblasts, Apert syndrome mutations do not increase cell proliferation (Lomri et al 1998;Fragale et al 1999;Lemonnier et al 2000) but alternatively, increase the expression of type 1 collagen, osteocalcin, and osteopontin, and enhance osteogenesis (Lomri et al 1998;Lemonnier et al 2000). This premature osteogenic cell differentiation induced by Apert Fgfr2 mutations is associated with increased N-cadherin expression and cell-cell adhesion (Lemonnier et al 2001b), which is reproduced by application of FGF2 (Debiais et al 2001).…”
Section: Control Of Cranial Suture Closure By Fgf Signalingmentioning
confidence: 99%